2022
DOI: 10.3390/ijerph19116515
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Depression and Post-Traumatic Stress Risk Following Miscarriage

Abstract: The experience of miscarriage is an important population-level problem that affects approximately 10–25% of pregnancies. The physical consequences of miscarriage have been researched extensively, but psychological sequelae less so. First-person accounts show that women who have experienced miscarriage feel pressured to stay silent, to grieve, and to fight intense physical and psychological challenges alone. There is ample scientific evidence on the links between miscarriage and physical and mental health disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…Another notable finding is the high number of miscarriages in our sample, as more than a third (33.8%) of women reported at least one prior miscarriage (range 0–7). This allowed us to examine the number of miscarriages as a continuous variable in path analyses, not a dichotomous or ordinal variable as in most prior research (e.g., Kukulskienė & Žemaitienė, 2022). Number of prior miscarriages was found to directly predict PPD.…”
Section: Discussionmentioning
confidence: 99%
“…Another notable finding is the high number of miscarriages in our sample, as more than a third (33.8%) of women reported at least one prior miscarriage (range 0–7). This allowed us to examine the number of miscarriages as a continuous variable in path analyses, not a dichotomous or ordinal variable as in most prior research (e.g., Kukulskienė & Žemaitienė, 2022). Number of prior miscarriages was found to directly predict PPD.…”
Section: Discussionmentioning
confidence: 99%
“…Some qualitative studies exist which describe trauma symptomology within the context of adverse reproductive events, yet these also remain few. In their qualitative study, Kukulskienė & Žemaitienė (2022) noted that seven women reported themes of trauma after miscarriage. Grauerholz et al (2021) indicated that a review of website blogs from female participants detailed symptoms of PTSD, relationship problems, and depression.…”
Section: Reproductive Trauma and Trauma Symptomologymentioning
confidence: 99%
“…Every adverse reproductive event is indeed a form of reproductive trauma, though each brings its own form of disenfranchised grief and emotional pain (Gozuyesil et al, 2020; Grauerholz et al, 2021; Volgsten et al, 2008). Though there are many forms of reproductive trauma, the most prevalent forms within the current literature include Infertility (Brigance et al, 2021; Jaffe, 2017), miscarriage (Kukulskienė & Žemaitienė, 2022), stillbirth (Gravensteen et al, 2013), fetal distress during delivery (Jotzo & Poets, 2005), fetal distress during pregnancy (Grauerholz et al, 2021), and premature birth (Gallus & Shreffler, 2009).…”
Section: Forms Of the Reproductive Trauma Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other losses, there are no standardised rituals to manage this grief, and there is often no physical manifestation of the loss to mourn (Fredenburg, 2017). Societal factors which discourage or make it difficult to openly acknowledge or publicly grieve pregnancy loss may leave women facing emotional and physical challenges alone (Kukulskienė and Žemaitienė, 2022; Rowlands and Lee, 2010). Stigma and misconceptions regarding pregnancy loss not only silence and obscure grief from others (Berry, 2022), but may also contribute to the maintenance of PTSD as the trauma memory is not updated, nor are negative beliefs challenged.…”
Section: Introductionmentioning
confidence: 99%